The post-Erdoğan vision of Turkish opposition: Opportunities and limitations - Edgar Şar (Stiftung Wissenschaft und Politik (SWP), 2023)
Nearly a year after its formation, the Nation Alliance, consisting of six opposition parties ("Table of Six"), finally started to act like a full-fledged electoral alliance against the ruling bloc under President Recep Tayyip Erdoğan. The six opposition leaders have long been criticised for failing to take concrete steps towards embodying a viable political alternative to the People's Alliance of the ruling Justice and Development Party (AKP) and the Nationalist Movement Party (MHP) since they publicly signed the joint manifesto for Turkey's transition into the "Strengthened Parliamentary System" in February 2022. Although the alliance has yet to announce its joint presidential candidate, it has manifested an unprecedentedly comprehensive joint platform in nine policy areas, including the rule of law, public administration, social policy, economy, and foreign policy. The 200-page joint document provides a comprehensive overview of what changes Turkey can be expected to go through in the short and medium terms should the Nation Alliance manage to defeat President Erdoğan's ruling bloc in the upcoming elections, which will probably take place on 14 May 2023. Even though it would not immediately offer a solution to various issues in Turkey-EU relations, a possible opposition victory could bring bilateral relations back to an institutional framework, whereby both parties can cooperate in a productive way to work out their problems and focus on common interests.
Keywords: 320; Turkey; elections; Nation Alliance; "Table of Six"; Recep Tayyip Erdoğan; Justice and Development Party (AKP); Nationalist Movement Party (MHP); European Union (EU)